Polish Physical Culture in Germany and the German Minority's Physical Culture in Poland until 1939 – A Comparative Study - Tomasz Jurek; Renata Urban (Central European Journal of Sport Sciences and Medicine, 2024)
The article represents the first attempt to depict the similarities and differences in the development of Polish physical culture in Germany and German physical culture in Poland during the interwar period of the 20th century. In both Poland and Germany, up until 1939, national minorities, notably the Germans in Poland and the Polish in Germany, played a significant role in fostering the development of physical culture. Drawing upon scholarly research and archival sources, commonalities between Polish physical culture in Germany and German physical culture in Poland can be discerned. They included: significant politicization, utilization for shaping patriotic attitudes and national integration, activity in the field of physical education, sports, and tourism, similar forms of activity of the Sokół Gymnastic Society in Germany and the German Turner Association in Poland, concern for the development of physical education among children and youth, and support from the respective home countries. However, notable disparities exist, including the longer-standing traditions of German physical culture on Polish soil, the considerably smaller scale of material support from Polish authorities for minorities in Germany, and the involvement of Deutsche Turnerschaft in Poland in a revisionist campaign against Poland in 1939.